Long Term Effects of Different Agro-forestry Systems on Soil Physical Health under Hilly Ecosystem of Meghalaya - Saha, R.; Mishra, V.K.; Tomar, J.M.S.; Kumar, Patiram (Indian Journal of Agroforestry, 2020)
Different agro-forestry systems (AFS) viz. Arboretum, Khasi mandarin, Assam lemon, Multistoried AFS (Alder + Tea + Black pepper), Silvi-horti-pastoral (Alder + Pineapple + Fodder) and Natural forest were evaluated to study the long-term effects on soil physical properties. These systems were developed in sloppy condition (30-50 % slope) at ICAR Research Complex for NEH Region, Umiam during 1987 - 1988. The soils were mostly clay to silty clay- in texture and acidic in reaction. After 15 years, soil bulk density of the various systems varied from 0.91 to 1.24 Mg m-3. Macro and micro aggregate percentage and mean weight diameter (MWD) were recorded in the order of natural forest> multistoried AFS > silvi-horti-pastoral > arboretum> Khasi mandarin> Assam lemon. The volume of residual pores (